Gradient of Land Cover and Ecosystem Service Supply Capacities- A Comparison of Suburban and Rural Fringes of Towns Dresden (Germany) and Poznan (Poland) - Łowicki, Damian; Walz, Ulrich (My University, 2015)
Quantifying landscape pattern and its change is essential for the monitoring of changes in ecosystem services caused by urbanization and other processes. Landscape indicators can be very useful for such assessments. The authors used landscape metrics for a gradient analysis of land cover between cities and protected areas. The two cities Dresden (Germany) and Poznan (Poland) were chosen, because they are comparable due to inhabitants, area and location in former socialistic regimes. The biggest difference affects legal and socio-economic conditions. Overall, the study shows decrease of ecosystem services and diversity indices with increasing distance from the protected area, but the lines of trend near Dresden and Poznan have a different course. In comparison to Poznan, around Dresden are more protected areas and much more settlement areas are located near or even inside them. Protected areas around Poznan are more aggregated and more distant from the town center, have character that is more natural and are more diversified in terms of land cover configuration. On the other hand, in Dresden, thanks the more compact character of built-up areas and accompanied green urban areas, the landscape of suburban zone is more diversified and the benefits of ecosystem services are closer to the people. The reason are more restrictive legal aspects of spatial planning in Germany.
Keywords: urbanization; ecosystem services; protected areas; landscape metrics; gradient analysis